Early Reading Difficulties : A Phenomena in Reading Problems - Bahrudin Bahrudin; Mohammad Arif Taboer; Sunardi Sunardi; Endang Rochyadi (Department of Special Education, 2020)
Reading Difficulties in one of challenging which faced by student in elementary school in Indonesia. This research purpose to find variety of challenging by student in early reading. 31 students with early reading problems who comes from 7 elementary school is use as respondent. Data collection is use by informal early reading test which validation with expert in special education needs and Bahasa Indonesia. Finding of this research is almost students with reading problems can read the letters, both vowel and consonant. They have problems in blending between letters become syllable and word.